INFLUENCE OF PLASMA-ELECTROLYTIC OXIDATION PROCESS TECHNOLOGICAL PARAMETERS OF ALUMINUM ON COATING GROWTH RATE - Posuvailo, V. M.; Vytvytskiy, V. V.; Romaniv, M. M.; Pryhorovska, T. O. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
There has been carried out an analysis of methods of oxide covering formation productivity increasing during plasma electrolytic oxidation of aluminum in electrolyte. There has been developed a technology of blank manufacturing and part strengthening by plasma electrolytic oxidation in the electrolyte, as well as the workbench has been modernized. There has been studied the process of oxidoceramic coating synthesis for the D16T aluminum deformed alloy of during plasma electrolytic oxidation in the electrolyte for different process parameters. It is established that the growth rate of oxidoceramic coating can be significantly increased by electrolyte component concentration involved in aluminum oxidation and rational choice of process electrical parameters. Hydrogen peroxide addition leads to obtained oxoceramic coating thickness increasing due to O, O2, OH, OH– concentration increasing in the electrolyte. It is established that the optimal concentration of H2O2 ranges from 5 g/l to 7 g/l. A further increase of peroxide concentration leads to a decrease in peroxide effect on oxoceramic coating growth rate on the D16T aluminum deformed alloy due to pH changes of the electrolyte and the deterioration of the oxide coating.